Computer simulations and experiments: The case of the Higgs boson. (August 2015) - Massimi, Michela; Bhimji, Wahid
Abstract: Simulations have been at the center of an important literature that has debated the extent to which they count as epistemologically on a par with traditional experiments. Critics have raised doubts about simulations being genuine experiments, on the ground that simulations seem to lack a distinctive feature of traditional experiments: i.e., the ability to causally interact with a target system. In this paper, we defend the view that simulations are indeed epistemologically on a par with traditional experiments. We first identify three possible ways of understanding the causal interaction claim . We then focus on the use of simulation in the discovery of the Higgs boson to show that in this paradigmatic case, simulations satisfy all three possible readings of the causal interaction claim.